1976
DOI: 10.3382/ps.0552319
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Depletion of Dieldrin in Visceral Fatty Tissue of Broilers

Abstract: White rock chicks were fed a commercial crumbles ration with approximately 1.0 p.p.m. of the active ingreient of technical grade dieldrin added to it. The treated feed was replaced by uncontaminated feed at various times from two to eight weeks of age. Equations were computed to describe the accumulation and depletion of the insecticide in visceral adipose tissue. Accumulations in females were described by polynomial equations with significant quadratic coefficients which indicated that the rate of accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The half-value time remained unchanged at 16 days. This half-value time is comparable to that of dieldrin reported by , 12 days, and Siegel et al (1976), about 2 weeks. In all cases, dilution in the growing broiler is the main factor in diminution although some metabolism or excretion must have taken place .…”
Section: Half-value Times In Broilerssupporting
confidence: 86%
“…The half-value time remained unchanged at 16 days. This half-value time is comparable to that of dieldrin reported by , 12 days, and Siegel et al (1976), about 2 weeks. In all cases, dilution in the growing broiler is the main factor in diminution although some metabolism or excretion must have taken place .…”
Section: Half-value Times In Broilerssupporting
confidence: 86%
“…Another explanation could be that their broilers were housed on the floor, whose contamination level also influenced the residues found. Recently, Siegel et al (1976) reported a difference in accumulation of dieldrin between broilers kept on the floor and those in cages. The effect was, however, probably mainly due to somewhat larger amounts of dieldrin in the feed during the floor trial and not to the management system.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies no attention was paid to possible sex differences in accumulation. However, recently Siegel et al (1976) reported a difference in accumulation pattern of dieldrin between male and female broilers.…”
mentioning
confidence: 96%
“…In previous reports we showed that after 6 weeks of age, White Rock (WR) males, whose feed contained low levels of dieldrin (1 mg/kg), tended to accumulate greater amounts of this chlorinated hydrocarbon in fatty tissue than females (Siegel et al, 1976;Siegel and Latimer, 1981). This difference was attributed partly to die greater percentage of carcass fat in the female than in the male, and was related to the lipogenic effects of estrogens (Lin et ah, 1980;Lorenz, 1954) in contrast to the protein anabolic effect of androgens (Kochakian, 1950).…”
Section: Introductionmentioning
confidence: 96%